2005
DOI: 10.1197/j.aem.2005.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Effects of Laser‐assisted Topical Anesthesia in a Porcine Model

Abstract: Objectives: A handheld laser device that removes the stratum corneum, the major barrier to transdermal absorption, has recently been approved to assist with topical anesthesia before painful procedures such as intravenous cannulation. The authors assessed the cutaneous histomorphologic effects of the laser device and the ability of the laser-treated skin to resist infection in a porcine model. Methods: This was a blinded, randomized animal experiment using isoflurane-anesthetized young domestic pigs. The ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…keloids and hypertrophic scars) (19). Therefore, we used the Singer classification for the histological evaluations of the wounds to quantify the cutaneous scars after transplantation of human mesenchymal stem cells (19). In this study, incisional wounds treated with hMSCs showed significantly less scarring than the control group.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…keloids and hypertrophic scars) (19). Therefore, we used the Singer classification for the histological evaluations of the wounds to quantify the cutaneous scars after transplantation of human mesenchymal stem cells (19). In this study, incisional wounds treated with hMSCs showed significantly less scarring than the control group.…”
Section: Discussionmentioning
confidence: 85%
“…While histological categorisation of scars into 'good' or 'bad' is subjective, few studies have attempted to develop a method by which this distinction can be made other than at the extreme end of the spectrum of healing (i.e. keloids and hypertrophic scars) (19). Therefore, we used the Singer classification for the histological evaluations of the wounds to quantify the cutaneous scars after transplantation of human mesenchymal stem cells (19).…”
Section: Discussionmentioning
confidence: 99%
“…The cytoplasm and intercellular region contained many vacuoles after treatment with both fluences. Vacuolization may be a sign of edema, which usually occurs with Er:YAG laser resurfacing [4,9]. Polymononuclear cell infiltration observed in the TEM image after 15 J/cm 2 treatment indicates an inflammatory phase, which is responsible for degradation of damaged tissue [23].…”
Section: Discussionmentioning
confidence: 94%
“…The occurrence for a short period of time post application of laser therapy in the treated groups in the present study is not surprising. Previous clinical studies and research reports have noted apparent increase in cutaneous and deep blood flow as a result of laser irradiation (Martine et al, 1991;Singer et al, 2005).…”
Section: Discussionmentioning
confidence: 95%